The factors of delay in claiming immovable property among residents in Shah Alam / Siti Nurul Sarah Rahim - Rahim, Siti Nurul Sarah (Academy of Contemporary Islamic Studies, 2018)
The problem of delays in estate claims is increasing from year to year. This phenomenon creates a number of issues that are increasingly critical and difficult to solve. If these properties were not developed, it would have given a huge loss to Muslims itself. This problem is due to the problem of inheritance management within the Malaysian Muslim community where they lack of understanding on the aspects of their property management. Moreover, Muslims are also less aware of the importance of making a will because they believe the property of the deceased can be managed through the faraid system. The negligence of Muslims in managing property will have an impact on the country's economic development as the property cannot be used appropriately. Hence, this study aims is to analyse the influence of the level understanding and the level awareness to the delay in claiming of immovable property and to determine the most significant factor in influencing the delay in claiming of immovable property. The method used is quantitative study where the respondents of this study were residents live in Shah Alam. Instrument that had been used are through a questionnaire and consists of 9 question items from section B and section C. Researchers had used the Statistical Package for Social Science version 20 (SPSS) to analyse raw data for frequency, percentage, correlation, and coefficient. As a result, the findings show that the most factor of delay in claiming immovable property are from the public level understanding. At the end of the study, several suggestions have been proposed to increase the level of understanding and awareness among Muslims.